FRI0344 IL-9 and CD4+Il9+ T Lymphocytes Are over Expressed in the Synovium of Patients with Rheumatoid Arthritis, Elicited in Vitro by Citrullinated Peptide Incubation and the Abrogation of Pu.1 in Mice Interfere with the Collagen Induced Arthritis. (10th June 2014) - Guggino, G.; Ciccia, F.; Rizzo, A.; Manzo, A.; Dieli, F.; Giardina, A.; Montecucco, C.; Alessandro, R.; Triolo, G.
Abstract : Background: Rheumatoid Arthritis (RA) is a chronic autoimmune disease characterized by joint erosion and damage. Several cytokines and recruitment of auto-reactive lymphocytes (characterized by a marked shift toward the Th1 and Th17 phenotype) to inflamed tissue is a defined feature of the disease. In addition to Th1/Th17 and Th2 cells, another subset of effector T cells, identified by the potent production of IL-9 and named Th9 cells, has been recently demonstrated. IL-9 was found in particular to be increased before the clinical onset of the articular disease in RA patients, and associated with the presence of RA-related autoantibodies and circulating biomarkers of inflammation. The exact role of Th9/IL-9 and related cytokines in RA however has not been yet adequately studied Objectives: To evaluate the role of IL-9 and IL-9-producing cells in patients with Rheumatoid arthritis and in a murine model of collagen-induced arthritis (CIA) Methods: IL-9, IL-9R and PU.1 expression was assessed by rt-PCR and IHC in the synovial tissue of RA and osteoarthritis (OA) patients. IL-9, IL-9R, IL-4, TSLP and TGF-b were investigated by immuno-histochemistry (IHC). Confocal microscopy was used to characterize the phenotype of IL-9-producing cells. The prevalence of Th-9 lymphocytes on peripheral blood mononuclear cells has been determined by flow cytometry analysis before and after incubation with citrullinated aggrecan (or not) peptide. Evaluation of CIA severity and IL-9 occurrence was also studied in normal and PU.1 deficient mice. Results: IL-9 was over-expressed in the RA synovial tissues and correlated with the degree of histological organization of B and T cells in ectopic tertiary lymphoid structures. IL-9 producing cells were demonstrated to co-express PU.1 and were thus identified as Th9 cells. Increased expression of IL-9R was also observed in RA, with diffuse positive cells detected outside T-B cell aggregates and few cells detectable at the outside border of lymphoid aggregates. Strong IL-4, TSLP and TGF-b (cytokines involved in the induction of Th9 polarization) expression was demonstrated by IHC in RA. Blood peripheral Th9 cells were also increased in RA and specifically activated by a citrullinated peptide. In the CIA mouse model, the abrogation of the Th9 transcription factor PU.1 ameliorated arthritis and was associated with low levels of IL-9 expression. Conclusions: Here we show for the first time that IL-9 and Th9 cells are over-expressed in the RA synovial tissue and correlated with the degree of histological organization of B and T cells in ectopic lymphoid structures. We also show that blood peripheral Th9 cells are increased in RA and in vitro expanded by citrullinated peptide incubation. Finally, in the CIA mouse model, the abrogation of the Th9 transcription factor PU.1 ameliorated arthritis. Altogether these results suggest that IL-9 and the Th9 cells may play an important role in the pathogenesis of RA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5190